Correlation of HER2 expression and clinicopathological characteristics in patients with urothelial carcinoma in China - WANG Shanshan, YE Dingwei, YANG Li, CHENG Fan, YANG Tiejun, ZHANG Xiaoping, YU Zhixian, ZHANG Qingyun, YANG Yong (Zhongguo aizheng zazhi)
Background and purpose: Human epidermal growth factor receptor 2 (HER2) is closely associated with drug efficacy and prognosis in urothelial carcinoma (UC). HER2 is a significant biomarker and therapeutic target in various tumors. In recent years, anti-HER2 antibody-drug conjugates have shown significant clinical efficacy in UC patients with HER2 overexpression. Therefore, an in-depth understanding of HER2 expression and its characteristics in Chinese UC patients is crucial to guide treatment decision-making, optimize treatment strategies and achieve personalized therapy. This study aimed to thoroughly investigate correlation of HER2 expression and clinicopathological characteristics in Chinese patients with UC. Methods: This study was a multicenter study that retrospectively included UC patients from urology departments of 8 tertiary hospitals in 5 geographical regions of China (North China, East China, South China, Central China and Northwest) whose tissue samples were collected from January 2023 to March 2024. Inclusion criteria: ① age above 18 years; ② UC diagnosed by histopathological or cytological examination; ③ complete results of HER2 expression detection using immunohistochemistry (IHC) in the primary tumor site were required. Exclusion criteria: ① diagnosed patients with tumors in other parts of the body; ② physicians evaluated other situations that were not suitable for inclusion in this study. IHC results for HER2 expression and clinicopathological data were collected. HER2 expression was determined according to the criteria outlined in “Clinical pathological expert consensus on HER2 testing in urothelial carcinoma in China”, with HER2 2＋ and 3＋ defined as HER2 overexpression. The HER2 expression and clinicopathological features were analyzed. This study was approved by the medical ethics committee of Fudan University Shanghai Cancer Center (ethical number: 2301268-12) and was registered at China Clinical Trial Registry (registration number: ChiCTR2300069746). Results: A total of 1054 patients with UC were included. Most of the tumors were bladder UC (n=807, 76.6%). The mean age of patients was (66.8±10.5) years, and the majority were male (78.5%). The HER2 overexpression rate was 58.4% (n=616), with an additional 23% of patients having HER2 1＋ expression (n=242), and a small proportion exhibiting negative HER2 expression (n=196, 18.6%). HER2 expression was significantly associated with various clinical and pathological characteristics such as Eastern Cooperative Oncology Group (ECOG) performance status, history of cardiovascular disease, history of metabolic disorders, smoking, UC disease location, differentiation grade, pathological type, and tumor stage. Conclusion: Retrospective analysis of multi-center data shows that HER2 expression is frequently observed in Chinese UC patients, with an overexpression rate of up to 58.4%. Furthermore, HER2 expression is closely associated with various clinical and pathological features of UC patients. This study underscores the critical importance of accurately assessing HER2 expression in UC patient to guide personalized therapies.